2017
DOI: 10.1007/s12328-017-0756-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic polyps formed like fundic gland polyps during long-term proton pump inhibitor administration

Abstract: We report a rare case of hemorrhagic gastric polyps resulting in anemia during long-term proton pump inhibitor (PPI) administration that endoscopically looked like a fundic gland polyp (FGP). A 44-year-old man presented complaining of anemia and tarry stools. Esophagogastroduodenoscopy (EGD) demonstrated multiple white edematous polyps in the corpus and antrum, which were considered to be FGPs. We attempted endoscopic hemostasis but hemorrhaging increased because of hemorrhagic polyps and vulnerable gastric mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Elderly patients are generally on more drugs than young patients [8], and therefore at greater risk of experiencing interactions between prophylactic drugs and other co-administered drugs [9]. Recent research has associated long-term oral PPI use with increased incidence of fundic gland polyps [10], increased risk of Clostridium difficile infections [11,12], and chronic diarrhea and collagenous colitis [13][14][15][16][17], suggesting that PPIs exert various negative effects on the digestive tract. Patients on PG drugs often experience diarrhea [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Elderly patients are generally on more drugs than young patients [8], and therefore at greater risk of experiencing interactions between prophylactic drugs and other co-administered drugs [9]. Recent research has associated long-term oral PPI use with increased incidence of fundic gland polyps [10], increased risk of Clostridium difficile infections [11,12], and chronic diarrhea and collagenous colitis [13][14][15][16][17], suggesting that PPIs exert various negative effects on the digestive tract. Patients on PG drugs often experience diarrhea [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that our patient had a history of long-term PPI administration for his gastroesophageal reflux disease. In recent years, the increased risk of gastric polyps during long-term PPI administration has been a growing concern [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on PPI-related gastric lesions have reported fundic gland polyps, hyperplastic polyps, and hemorrhagic polyps formed like fundic gland polyps [6,7]. Furthermore, diffuse changes associated with PPI use, specifically gastric cracked and cobblestone-like mucosa, have also been reported in the region of the gastric corpus glands [8].…”
Section: Discussionmentioning
confidence: 99%